Migration: A Response to the Transmigration program for Female Jamu Gendong Sellers - Sunaniah; Idham Irwansyah Idrus; Ulfa Utami Mappe (Tinta Emas Publisher, 2025)
Religion and culture dogma teaches that men have the responsibility an also the main role in the stability of the family economy. However, practically economic stability in each family cannot be separated from the women role, especially women who decided to work. In a patriarchy culture, women still occupy the subordinate position compared to men. Currently there are many women who participate in supporting the family economy. Even though they dared to take a double role in the family, in reality they remained in a limp position